Echoes of Justice: The Impact of Laudato Si and Laudate Deum on Addressing Injustice in Our World - Diarsa, Leo Kristian Eka Putra; Haq, Mochamad Ziaul (UIN Sunan Gunung Djati Bandung, 2024)
This study examines and highlights the relevance of Laudato Si’ and Laudate Deum in addressing injustice within the context of environmental degradation. The researcher argues that these documents provide profound moral perspectives that frame environmental issues not merely as ecological challenges but as manifestations of injustice affecting humanity as a whole. A qualitative approach was employed, combining descriptive qualitative and comparative methods. The study involves an in-depth exploration of Pope Francis's thoughts on justice in Laudato Si’ and Laudate Deum, utilizing literature reviews of Church documents and the Pope's personal history. The findings reveal that Pope Francis integrates social and ecological justice within a framework of integral ecology, emphasizing the interconnectedness of humanity and creation. Drawing from John Rawls's distributive justice and Brian Baxter's ecological justice theories, the study explores how these perspectives are reflected in the papal encyclicals. While Rawls focuses on the fair distribution of rights and duties within social institutions, Baxter extends justice to non-human entities. Pope Francis synthesizes these ideas, advocating for social inclusion and ecological stewardship as responses to exploitation and inequality. The study underscores the holistic approach of Pope Francis, where justice encompasses the dignity of the marginalized and the protection of the environment. His teachings challenge technocratic paradigms and call for collective responsibility to create a more just and sustainable world. By bridging social and ecological concerns, Laudato Si’ and Laudate Deum offer critical insights for addressing environmental degradation as an issue of moral and social justice.